ENVIRONMENTAL PORTRAIT OF THE CANANEIA-IGUAPE ESTUARINE LAGUNAR COMPLEX: THE INFLUENCE OF THE VALO GRANDE CHANNEL - Nery, Liliane Moreira [UNESP]; Perucello, Jaqueline De Lima [UNESP]; Cunha-Lignon, Marilia [UNESP]; Machado, Levi Pompermayer [UNESP]; Da Cunha E Silva, Darllan Collins [UNESP] (Univ Fed Parana, Editora, 2024)
Due to its essential and multiple uses, the prevention of water body quality is crucial for the maintenance of the numerous living organisms presents in them. In this regard, the study was conducted with the aim of evaluating the physicochemical parameters of water and sediments in the Canan & eacute;ia-Iguape Estuarine-Lagoon System (CIELS), located on the southern coast of S & atilde;o Paulo, with a focus on the impacts of the artificial Valo Grande channel. To achieve this, physicochemical parameters were analyzed in both water and sediment samples, revealing increased conductivity and decreased dissolved oxygen and pH in regions closer to the channel. The alkalinity, sulfate, and hardness concentrations showed substantial variations as the distance from Valo Grande increased. Regarding the sediments, the absence of salinity and the higher water retention capacity in mangrove areas reinforce that Valo Grande interferes with the environmental dynamics of CIELS. Therefore, it is recommended to propose studies addressing the implementation of an applied environmental monitoring plan, considering both the physicochemical and biological aspects, given the socioenvironmental and economic importance of CIELS.
Keywords: Water; Sediment; Spatial analysis; Ribeira Valley